The Impact of Informality on Inclusive Growth in Developing Countries: Does Institutional Quality Matter? - Jan, Meer; Baloch, Amdadullah; Bawazir, Abdullah Abdulaziz; Qayyum, Abdul; Qatawneh, Mohammad Abdelhamid Salem (International Journal of Economics and Financial Issues, 2025)
Inclusive growth, a critical measure of national progress, has gained significant attention from policymakers due to the persistent issues of income inequality and poverty despite economic growth. This paper explores the impact of informality on inclusive growth in developing countries and mediating role of institutional quality on inclusive growth-informality nexus. For empirical analysis, the study employs the system GMM approach to examine how informality affect inclusive growth over the period 2008-2020. An inclusive growth index is constructed using the social opportunity function, and since inclusive growth is a multidimensional concept, multiple variables are used to better capture its different facets of inclusive growth. These variables include the Human Development Index (HDI), the Gender Inequality Index (GII), carbon emissions, income growth of the bottom 40% (Growth 40), and real GDP per person employed. The empirical findings revealed that informality, such as vulnerable, dynamic general based measure of informal economy and MMIC-based measure of informal economy, negatively affects inclusive growth, with self-employment showing an insignificant impact. Importantly, institutional quality plays a crucial mediating role in the relationship between informality and inclusive growth. Further the study also construct indifference curves for selected developing countries to show their growth inclusiveness. Finally, the study suggests policies to promote innovative activities, improve the institutional framework, and encourage formalization to enhance inclusive growth in developing countries.